Stress, phase stability and oxidation resistance of ternary Ti-Me-N (Me = Zr, Ta) hard coatings - Abadias, Gregory; Koutsokeras, Loukas E.; Siozios, Anastasios; Patsalas, Panos (My University, 2013)
In this work, we comparatively study the phase formation, stress development, thermal stability and oxidation resistance of two ternary transition metal nitride systems, namely Ti-Zr-N and Ti-Ta-N, in the whole compositional range. Thin films, with thickness up to 300 nm, were synthesized by reactive magnetron sputter-deposition in Ar + N2 plasma discharges at 300 C from elemental metallic targets. The energy distribution of energetic species is considered based on Monte-Carlo simulations (SRIM + SIMTRA codes). The origin of stress build-up during growth is addressed by combining in situ wafer curvature and ex situ X-ray diffraction (XRD) techniques. For as-deposited films, a unique dependence of growth morphology, grain size, preferred orientation and compressive stress evolutions on growth energetics is revealed, independently of the system. The phase stability upon vacuum and air annealing up to 850 C was followed using in situ temperature XRD, ex situ X-ray Photoelectron Spectroscopy and optical reflectivity, while the morphological evolution was characterized using field emission scanning electron microscopy.
Keywords: Magnetron sputtering; Transition metal nitrides; TiZrN; TiTaN; Stress; Thermal annealing